PERLINDUNGAN HUKUM TERKAIT ADANYA INDIKASI PENYALAHGUNAAN WEWENANG OLEH OKNUM DIRJEND KI KEMENKUMHAM DALAM SENGKETA PATEN - Wardoyo, Hadi; Marwenny, Elwidarifa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2024)
Abuse of authority which is a right owned by Government Agencies and/or Officials and other state administrators to take decisions and/or actions in administering government. In this case also Abuse of authority is the use of authority by Government Agencies and/or Officials in taking decisions and/or actions in government administration carried out by exceeding authority, mixing up authority, and/or acting arbitrarily as intended in Article 17 and Article 18 of Law Number 30 of 2014 concerning Government Administration. And states the aspect of authority where the problem lies in whether the official who issued the letter has the authority or does not have the authority to issue the letter based on existing regulations. And when issuing decisions, officials should have authority and if they do not have authority, they are prohibited from issuing decisions. Therefore, this statement is also in accordance with the provisions of Article 1 point 22 of Law No.30.